Проблеми керованості для рівняння неоднорідної струни, закріпленої на правому кінці - Халіна, К.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The wave equation for a non-homogeneous string on a segment is considered. The right end point is .xed. On the left end point, L^∞-control that is bounded by a given constant is considered. Necessary and su.cient conditions of null- and approximate null-controllability for this system are found. Moreover, the control that solves the formulated problem is found explicitly.